Simulated cusp ion dispersions and the day-side magnetopause reconnection rate - Burkholder, Brandon L.; Chen, Li-Jen; Dorelli, John; Ma, Xuanye; da Silva, Daniel; DesJardin, Ian; Huang, Yi-Min; Bessho, Naoki; Sorathia, Kareem A. (Frontiers in Astronomy and Space Sciences, 2025)
When the interplanetary magnetic field (IMF) is southward dominant, antiparallel day-side magnetic reconnection occurs near the equatorial magnetopause, and the reconnection rate quantifies how much magnetic flux is removed from the magnetosphere per time. During space weather events, this is a key quantity to understand, because the day-side magnetopause can be significantly eroded, potentially receding within geosynchronous orbit. However, direct observations of the reconnection rate are challenging, so attempts have been made to quantify the reconnection rate through remote measurements. In particular, ion dispersions observed in the low-altitude cusp have been connected to the day-side magnetopause reconnection rate, assuming the dispersions are formed by time-of-flight differences for different energy particles convecting with the same field line. This provides a promising avenue to probe the day-side reconnection rate with satellites that pass through the low-altitude cusp, like Defense Meteorological Satellite Program (DMSP) and Tandem Reconnection and Cusp Electrodynamics Reconnaissance Satellites (TRACERS). In this study, cusp ion dispersion signatures are constructed using the forward particle tracing capability of the GAMERA-CHIMP global magnetohydrodynamics (MHD) with test particle framework. Under idealized solar wind driving with steady southward IMF, the reconnection rate is calculated and compared with an independent measure of the reconnection rate based on the amount of magnetospheric flux reconnected per time. Changes in magnetospheric flux content indicate the day-side magnetopause reconnection rate is ∼0.65 mV/m with variations up to 0.2 mV/m occurring on a ∼5 minute timescale which are associated with the formation and evolution of magnetic flux ropes. Reconnection rates calculated from simulated cusp ion dispersions are mostly in the range 0.2–1.4 mV/m. These values corresponding to idealized solar wind driving conditions provide a benchmark for future case studies. Ultimately, the goal of this study is to demonstrate how the reconnection rate can be calculated from simulated cusp ion dispersions.